The Use of Natural Sap Preservatives Made from Green Betel Leaf and Lime on the Quality of Block Coconut Sugar - Karseno, Karseno; Haryanti, Pepita; Asriningtias, Harlin Citra (Indonesian Journal of Food Technology, 2025)
microbial activity. The damage of coconut sap can be prevented by using natural sap preservatives such as betel leaf and lime. Purpose: This study aims to determine the the percentage of betel leaf powder to total natural preservation and the amount of its use into 1 L coconut sap that produces the best quality of block coconut sugar. Method: This study used a Completely Randomized Design with 3 replications. The factors tested were the percentage of betel leaf powder to total of preservation (w/w), namely 2,5%, 5%, 7,5% dan 10% and the amount of preservative used in 1 liter of coconut sap was 1g and 2g. The parameters of sap and coconut sugar that observed were the pH of coconut sap, moisture, reducing sugar, ash and texture of block coconut sugar. The sensory parameter that observed were color, betel aroma, betel taste and preference for the taste of block coconut sugar. Result: The results showed that percentage of betel leaf powder of 7.5% to total preservation with addition of 1 g/L of coconut sap produced the best quality of block coconut sugar.